Pkm Pendampingan Warga Stunting untuk Menurunkan Angka Stunting Sesuai Amanah Peraturan Presiden Nomor 72 Tahun 2021 tentang Percepatan Penurunan Stunting - Ismail, Ismail; Hutama Hutabarat, Dany Try; Bahmid, Bahmid (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Stunting is a disruption in the growth and development of children due to chronic malnutrition and recurrent infections, which is characterized by their length or height being below the standards set by the minister who handles government affairs in the health sector. The number of stunted children under five in Indonesia will decrease to 21.6% in 2022. The factors of stunting are maternal education, family income, maternal knowledge about nutrition, exclusive breastfeeding, age at complementary feeding, zinc and iron adequacy levels, history of infectious diseases and genetic factors. By considering these factors, it can be concluded that if the decline that occurs in 2022 is not controlled as well as possible, there could be another increase in the number of stunting sufferers in 2023. This community-based empowerment aims to continue the success that has been achieved in reducing stunting rates in 2022 and to spread and expand education for the community regarding stunting. The output of this empowerment is none other than to help and contribute to reducing the stunting rate which can be obtained by increasing mothers' knowledge about the important nutrients needed by their children, not only mothers. It is hoped that by carrying out this empowerment, people's knowledge about stunting will no longer be just scientific knowledge but has become a habit and general knowledge. Outputs in the field of scientific publications in this service will be published in sinta-4 indexed journals in service journals. So that through this community service and the output that will later be published we can provide real knowledge to society.